COMPARATIVE ANALYSIS OF THE CHANGE OF THE STRUCTURE AND PROPERTIES OF METALS WITH GTSK-GRATE AFTER ROLLING BY STANDARD AND T-D TECHNOLOGIES - A. A. Tolpa; E. G. Pashinkaja; A. I. Maksakov; S. I. Marchuk; I. I. Tishchenko (Литьë и металлургия)
The actual problem of the compound stress influence on the formation of the structure and characteristics of metals is studied. It is shown, that the formed after experimental rolling structure is notable for high degree of blending and uniformity and less pronounced anisotropy of characteristics and structure along the deformation axle direction.